ANALISIS PENYELESAIAN PEMBIAYAAN BERMASLAH PADA PT. BAK MUAMALAT INDONESIA PERSERO , TBK CABANG PEMBANTU KOLAKA - Harysah Damar Rahmadani (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Islamic banks are financial institutions that function as intermediaries for excess funds and parties lack funds for business activities and other activities in accordance with Islamic law. Islamic Bank in international terms known as Islamic Banking or Interest Free Banking is a banking system which in its operational implementation does not use the interest system (usury), speculation (maysir), and uncertainty or obscurity (gharar). For those who have concerns about the three elements, Islamic banks can be an alternative as a means of lending capital or to invest funds because the type of business of Islamic banks is as a financial intermediary that can be run into funding and financing. One of the factors in the occurrence of problematic financing is due to default, poor customer character, or a decrease in income from business results and natural disasters and the settlement carried out by Bank Muamalat in dealing with troubled financing, namely restructuring by rescheduling by extending the repayment period , changing requirements by reducing the amount of obligations that must be paid or by adding customer capital, selling collateral, voluntary collateral or auction.